2021
DOI: 10.3390/en14206683
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Pressure Fluctuations in the S-Shaped Region of a Pump–Turbine

Abstract: Hydraulic pumped storage is a special power generation and electricity shortage technology, which is usually operated with thermal power and nuclear power units, and plays a key role in ultra-high voltage and smart grid. Pressure fluctuations are the main reasons for the instability of the S-shaped region of pump–turbines, which seriously affects their lifespan and operation stability. To reveal the mechanism and propagation law of pressure fluctuations in the S-shaped region as well as numerical simulations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…They also found that the dominant frequency of pressure pulsation in the vaneless area was the high-frequency component of the vane frequency, while the dominant frequency of the draft tube vortex zone was lower [24]. Researchers [25][26][27][28][29] considered that the internal flow characteristics were closely related to pressure pulsation, and the reflux and vortex generated in the flow could lead to violent pressure pulsation.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the dominant frequency of pressure pulsation in the vaneless area was the high-frequency component of the vane frequency, while the dominant frequency of the draft tube vortex zone was lower [24]. Researchers [25][26][27][28][29] considered that the internal flow characteristics were closely related to pressure pulsation, and the reflux and vortex generated in the flow could lead to violent pressure pulsation.…”
Section: Introductionmentioning
confidence: 99%
“…For the study of S-shaped region, Wang et al [4] studied the pressure pulsation mechanism under turbine brake conditions and reverse pump conditions, and found that there are high amplitude and low frequency pressure pulsations under these two conditions, which are caused by reflux and vortex in vaneless space respectively. Kinoue et al [5] studied the start-up process of low specific speed pump turbines and found that the internal flow pattern in S-shaped region was very disordered.…”
Section: Introductionmentioning
confidence: 99%
“…For a large amount of high residual pressure liquids in industries such as petrochemical, petroleum processing, seawater desalination, and steel metallurgy, pressure-reducing valves or orifice plates are usually used to reduce these fluids to the required low pressure, which means that large pressure energy in fluids is wasted [1][2][3][4][5][6]. To reduce energy waste, some enterprises use hydraulic turbine devices to recycle and utilize pressure energy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%